2009
DOI: 10.1182/blood-2009-03-211342
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stem and progenitor cell contribution to neovasculogenesis is dependent on model system with SDF-1 as a permissive trigger

Abstract: Adult bone marrow (BM) contributes to neovascularization in some but not all settings, and reasons for these discordant results have remained unexplored. We conducted novel comparative studies in which multiple neovascularization models were established in single mice to reduce variations in experimental methodology. In different combinations, BM contribution was detected in ischemic retinas and, to a lesser extent, Lewis lung carcinoma cells, whereas B16 melanomas showed little to no BM contribution. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 36 publications
(85 reference statements)
1
36
0
Order By: Relevance
“…In our hands, however, disruption of this immediate VDA-induced CEP peak using DC101 or another antiangiogenic agent (sunitinib) was not observed. The variations in CEP levels reported herein were synchronized with changes in levels of G-CSF, MMP-9, and SDF-1, 3 key proteins known to orchestrate CEP mobilization (21,31,43,48,49). Interestingly, although antiangiogenic strategies had no effect on the initial CEP peak, their administration after CA-4-P completely abrogated the late CEP burst and showed the most potent antitumor activity with concomitant disruption of GFP + bone marrow-derived cell tumor infiltration.…”
Section: Cancer Patients Treated With Vdas Display Acute Peaks In Cecmentioning
confidence: 82%
See 1 more Smart Citation
“…In our hands, however, disruption of this immediate VDA-induced CEP peak using DC101 or another antiangiogenic agent (sunitinib) was not observed. The variations in CEP levels reported herein were synchronized with changes in levels of G-CSF, MMP-9, and SDF-1, 3 key proteins known to orchestrate CEP mobilization (21,31,43,48,49). Interestingly, although antiangiogenic strategies had no effect on the initial CEP peak, their administration after CA-4-P completely abrogated the late CEP burst and showed the most potent antitumor activity with concomitant disruption of GFP + bone marrow-derived cell tumor infiltration.…”
Section: Cancer Patients Treated With Vdas Display Acute Peaks In Cecmentioning
confidence: 82%
“…Although in some preclinical studies authors have shown the incorporation of CEPs in tumor neovessels (24)(25)(26)(27), the contribution and general relevance of CEPs to tumor angiogenesis and progression have been controversial and the subject of intense scrutiny as the result of several studies in which investigators reported contradictory data (28)(29)(30)(31)(32). Alternatively, in other preclinical studies, authors have suggested that CEPs are not only key contributors to tumor neoangiogenesis and tumor growth (24)(25)(26) but are also critical regulators of the angiogenic switch promoting metastatic progression (33).…”
Section: Vda-induced Tumor Vascular Disruption Correlates With Peaks mentioning
confidence: 99%
“…These investigators quantified the levels of vascular endothelial growth factor and SDF-1 in the vitreous of patients with retinal detachment (RD) and proliferative diabetic retinopathy as well as other pathologies. Vascular endothelial growth factor and SDF-1 levels are increased in proliferative diabetic retinopathy; 16,17 however, only SDF-1 levels were increased in RD. Interestingly, the up-regulation of SDF-1 in RD did not lead to proliferation of the vasculature of the retina.…”
mentioning
confidence: 99%
“…Recent elegant experiments using multiple model systems to evaluate angiogenesis in mice confi rm that bone marrow stem cells make a signifi cant contribution to neovascularization and that this is dependent on the nature of the extent of the disease. Thus, there is evidence that the more the severe the ischemia the greater the contribution of bone marrow stem cells to the vasculogenesis [ 67 ] .…”
Section: Mobilization Of Epcsmentioning
confidence: 99%